132, 173‐Cyclopheophorbide b enol as a catabolite of chlorophyll b in phycophagy by protists. Issue 16 (4th July 2013) - Kashiyama, Yuichiro; Yokoyama, Akiko; Shiratori, Takashi; Inouye, Isao; Kinoshita, Yusuke; Mizoguchi, Tadashi; Tamiaki, Hitoshi
Abstract : Both 13 2, 17 3 ‐cyclopheophorbide a and b enols were produced along with ingestion of green microalgae containing chlorophylls a and b by a centrohelid protist (phycophagy). The results suggest that chlorophyll b as well as chlorophyll a were directly degraded to colored yet non‐phototoxic catabolites in the protistan phycophagic process. Such a simple process by the predators makes a contrast to the much sophisticated chlorophyll degradation process of land plants and some algae, where phototoxicity of chlorophylls was cancelled through the multiple enzymatic steps resulting in colorless and non‐phototoxic catabolites. Abstract : A novel chlorophyll b (Chl‐ b ) derivative was found from phycophagic protists. The derivative was identified as 13 2, 17 3 ‐cyclopheophorbide b enol (cPPB‐ b E). cPPB‐ b E co‐occurred with Chl‐ a ‐derived cPPB‐ a E by preying on Chl‐ a / b algae. cPPB‐ b E is likely to be a de‐phototoxicified catabolite of Chl‐ b, similarly as cPPB‐ a E. Chl‐ b is directly catabolized along protistan phycophagic processes, unlike in land plants.